Functional Analysis for Gauge Fields on the Front-Form and the Light-Cone Gauge - Pimentel, B. M. [UNESP]; Suzuki, Alfredo Takashi [UNESP]; Zambrano, G. E. R. (Springer Wien, 2012)
Constrained systems in quantum field theories call for a careful study of diverse classes of constraints and consistency checks over their temporal evolution. Here we study the functional structure of the free electromagnetic and pure Yang-Mills fields on the front-form coordinates with the null-plane gauge condition. It is seen that in this framework, we can deal with strictu sensu physical fields.